REPORTS TO STOCKHOLDERS. - Sanders, T. H. (The Accounting Review, 1934)
The article presents a report to stock holders reflecting the findings of the Committee on Statistical Reporting and Uniform Accounting for Industry, for presentation to the Business Advisory and Planning Council for the Department of Commerce, with respect to the financial reporting of corporations to their stockholders. The Committee has surveyed the area of activities referred to it with a view to determining both the relative importance and the urgency of the several problems that are arising. The field covered by the words 'uniform accounting' is extensive. Many phases of accounting theory and practice are still in a controversial stage. The conclusion was inescapable that if the Committee hoped to accomplish any practical results it should limit the scope of its inquiry to one or two subjects which offered possibilities for tangible accomplishments within a reasonably short space of time. Business life by investment and the desirability of having it conducted upon the soundest basis possible, very soon brought to fore the question of the published reports by which listed companies furnish financial information to their stockholders and to the business public generally.